Polarization Discontinuity and Interface Charges in Ferroelectric Superlattices. Issue 1 (2nd January 2016) - Chew, Khian-Hooi; Lim, Kok-Geng; Ong, Lye-Hock
Abstract : Effects of polarization discontinuity and interface screening charge in superlattices composed of alternating ferroelectric and dielectric layers are studied based on Landau-Ginzburg theory. Interface mixing gives rise to polarization continuity or discontinuity in the superlattices. At interfaces, screening charge with equal and opposite sign accumulates at alternate interface to compensate the depolarization field in the superlattice. The alternative appearance of interface screening charge induces internal electric fields in the individual layer. Our study reveals two possible charge compensation mechanisms by which the screening charge may build up at interfaces, depending on the arrangement of screening charge at interfaces. The screening charge may build up at interface to induce an internal field that acts against the depolarization effect in the constituent layer. Another compensation phenomenon is that the built-up charges suppress the inhomogeneous polarization near to interface, forming a superlattice with a uniform polarization across the constituent layer. Effects of interface screening charge on the properties of superlattice with polarization discontinuity are examined by looking at the polarization and internal field profiles. Polarization and internal electric field as a function of interface charge density for superlattices with different thicknesses are also discussed.